Gender Mainstreaming and Technology Application: An Appraisal of TANWA Project - Ponnusamy, K.; Srinath, Krishna; Meenakshi, S.; Saha, Geeta (Indian Journal of Extension Education, 2015)
The project “Tamil Nadu Women in Agriculture” (TANWA) was launched in 1986 aimed at technological empowerment  of farm women. An impact study was conducted in 2013 to understand the technology application and gender  empowerment in Kancheepuram district of Tamil Nadu after more than 10 years of project termination. TANWAbuilt up  an effective system for the training of farm women with help of specially recruited female extension staff. Farm women  groups widened the scope of their work by taking up savings and other income generating activities. The trained farm  women adopted a range of agricultural skills leading to increase the yields of main crops, greater marketable surplus and  savings on chemical fertilizers. The influence of women in farm matters goes more or less hand in hand with an increase in  their influence over family matters. The project had brought a good degree of gender sensitization at household level while  building women's capacities as skillful and self-confident farmers. The formation of farm women groups had contributed  greatly to the continued viability of some of the income generating activities as well as providing a forum for learning,  innovating and extending mutual support among them. Similar attempts elsewhere could enhance the performance of  farm women from small and marginal farms in their roles as agricultural producers leading to increased productivity,  income and food security.
Keywords: Gender mainstreaming; Technology application; TANWA; Women empowerment; development